The Psychological Well-Being of Non-ASN Contract Workers in Padang City - Rahmat Hidayat (CERDAS AKADEMIKA NUSANTARA, 2026)
The results of this study indicate that character strengths and social support play a significant role in improving the psychological well-being of uncertified private lecturers in Padang City. Data that meet the assumptions of normality and linearity ensure the validity of these findings. Positive character strengths and strong social support that lecturers receive can stabilize their psychological well-being, while weak character and minimal social support have the potential to reduce well-being and increase work stress. These findings confirm that interventions focused on strengthening lecturers' character, such as developing perseverance, optimism, and emotional regulation skills, as well as increasing social support from colleagues, leaders, and family, have the potential to be effective strategies for improving the psychological well-being of uncertified lecturers. This study encourages increased understanding of the various psychological elements that directly impact lecturer well-being and highlights the urgency of developing mentoring and training programs based on character strengths and social support within private higher education institutions. Furthermore, these results open up opportunities for further research by including other variables such as self-efficacy, job satisfaction, and institutional support to more broadly describe the determinants of psychological well-being among lecturers in various higher education contexts.